Public Health and Biological Risks: An integrative review on infectious diseases in meat processing industry workers (Research, Society and Development, 2025)
Occupational infectious diseases are a growing challenge for public health, especially among workers in the meatpacking industry, who are continuously exposed to biological agents of epidemiological relevance. Recent evidence shows a high prevalence of zoonoses such as leptospirosis, bovine tuberculosis and brucellosis, directly associated with the structural, sanitary and operational conditions of these environments. In view of this scenario, the objective of this study was to carry out an integrative review on biological risks and the occurrence of infectious diseases among workers in the meatpacking industry, identifying patterns of vulnerability, transmission mechanisms and structural gaps that explain the persistence of these diseases in the sector. An integrative literature review was carried out, with searches in the PubMed, Scopus, ScienceDirect, Web of Science, EMBASE, Google Scholar, EBSCO Medline, and VHL databases, including studies published between 2019 and 2024. The results showed that the seroprevalence of leptospirosis ranged from 16% to 28% in workers and slaughtered animals, while bovine tuberculosis reached up to 18.4% of the records analyzed. Hygiene failures, poor adherence to the use of PPE, and inadequate infrastructure were identified as critical factors that amplify biological risk. It is concluded that integrated interventions, improvements in biosafety, professional training and continuous epidemiological surveillance are essential, recommending new longitudinal and comparative studies to strengthen preventive strategies in the sector.